Surplus Water Potential Of Himalayan Agro-Climatic Region In India - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRACT Under characteristic agro-climatic conditions, in contrast to those of the other physiographic regions of Indian sub-continent, Himalayan agro-economy is somehow different. Specific nature of rainfall pattern and distribution provides sufficient amount of surplus water which can be utilized for the irrigation purposes during the moisture stress periods. The present attempt has been designed to evaluate the possibilities and potentials of surplus water, obtained during rainy season and winter rains, for irrigation during moisture stress periode for the wheat crop in U.P. Himalaya.